Age-Related Anatomical Changes in the Upper Limb Musculoskeletal Structures among Elderly Pakistani. A Cross-Sectional Study - Irum Naz, Farhana Jafri, Asma Zulfiqar, Sitwat Amna, Amber Salman, Saba Saleem Safdar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anatomical deterioration of musculoskeletal structures is a major issue for elderly populations, most notably in the upper limbs. This study investigates these age-related changes and their clinical implications among elderly Pakistani individuals. Aims and Objectives: The aims and objectives were to identify age-related anatomical changes in upper limb musculoskeletal structures among elderly Pakistani individuals. The objective is to evaluate clinical implications for better geriatric healthcare practices. Methodology: A descriptive cross-sectional study was carried out for 12 months involving n=200 elderly Pakistani participants. DXA scans, clinical examinations, upper limb musculoskeletal ultrasonography, and X-rays were used to evaluate upper limb musculoskeletal structures. Structured questionnaires were used to collect demographic and clinical data. Descriptive statistics and comparative tests were used for data analysis with SPSS version 26.0, considering p≤0.05. Results: In elderly participants, the study found the loss of significant amounts of muscle (sarcopenia) in 71 percent, with an average mean grip strength of 18.5 kg. Pervasive degeneration of the joint included osteoarthritis (51%), ligament laxity (43.5%), and tendon thinning (61%). Osteopenia/osteoporosis as seen on radiographic imaging was present in 58% of patients with bone mineral density markedly reduced in proximal Humerus and distal radius. Significantly, higher age, female gender, and lower physical activity correlated with more anatomical deterioration. Functional impairment was present in 64% of the participants and resulted in daily activities. Conclusion: Anatomical changes were observed in upper limb musculoskeletal structures among elderly Pakistanis making them functionally independent. These findings point towards the importance of having preventive and rehabilitative strategies tailored to geriatric healthcare. Keywords: Anatomical, Musculoskeletal, Rehabilitative, Osteopenia, Osteoporosis